They Not Like Us: A Story about Racioethnicity and Psychological Well-Being - Pamela Braboy Jackson (Journal of Health and Social Behavior, 2026)
There is a broader tendency to understand research on minority mental health using a “they” versus “us” historical backdrop. Across time, the “minority paradox” emerged as a contemporary example of the way othering has positioned research to better understand why minorities have the same or better mental health rather than why non-Latino whites have poor mental health. I examined the association between racioethnicity and the lifetime prevalence of mental disorder using data from the Collaborative Psychiatric Epidemiology Studies (N = 19,840). Most racioethnic minorities had lower prevalence of mood, anxiety, and substance use disorder than non-Latino whites, a pattern consistent with decades of past and contemporary research. I argue a more appropriate label of these research findings would be a “white mental disorder paradox” rather than a minority paradox and provide recommendations for future research that could help explain poor mental health reported by non-Latino whites and adults of Puerto Rican descent.